Application of Visual Project Management to build a pro-sustainability design tool (ModaPalavra e-periódico, 2021)
The article aims to present the application of Visual Project Management in the construction of a pro-sustainability project tool with an emphasis on the mitigation of solid textile waste. This is the Zero Waste Tool for Apparel Design (ZWTAD). The construction of the tool took place in two stages: (I) initially, based on the use of the visual panel of the Orientation Guide for Project Development; and (II), then, under the application of the structural elements (premises, requirements and usability principles) of Visual Project Management. Therefore, methodologically, this article can be understood as applied, descriptive, bibliographic and qualitative research. It is inferred that the development of the ZWTAD can constitute a case of Visual Project Management, however, for now, it is still an incomplete visual model.
Keywords: visual project management; design tools; Zero Waste Design